PECULIARITIES OF TEACHING PRONUNCIATION TO YOUNG LEARNERS - Pardayeva Aziza Raxmatilloyevna Aliyeva Zebo (Galaxy International Interdisciplinary Research Journal, 2021)
Previous facts, this qualitative study aims at introspecting the role of explicit instruction for the teaching of pronunciation to young learners in ten primary schools in Pérez Zeledón. To gather meaningful data, questionnaires, structured observations and artifact collection were some of the instruments used. Language teachers were the main informants in this study. After results were obtained and analyzed, researchers decided to suggest a deductive model to teach vowel sounds pronunciation to primary school learners that follows key principles of the experiential approach.